Evaluation of the Hypotensive Preterm Infant: Evidence-Based Practice at the Bedside? - Elizabeth Murphy; David B. Healy; Roberto Chioma; Eugene M. Dempsey (MDPI AG, 2023)
Choosing the appropriate management approach for the preterm infant with low blood pressure during the transition period generally involved intervening when the blood pressure drifted below a certain threshold. It is now clear that this approach is too simplistic and does not address the underlying physiology. In this chapter, we explore the many monitoring tools available for evaluation of the hypotensive preterm and assess the evidence base supporting or refuting their use. The key challenge relates to incorporating these outputs with the clinical status of the patient and choosing the appropriate management strategy.